The mediating role of work engagement and work reflection between the relationship of inclusive leadership and work-family positive spillover - Sabeen Andleeb; Ahmad Usman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
Current study investigated a serial mediation model utilizing conservation of resources theory (COR) in which inclusive leadership predicts the work family positive spillover through work engagement and work reflection. Extending the prior research studies on work reflection, the present study intends to test the effect of resources that are created at workplace (inclusive leader behaviors and work engagement) on personal life of employees. Employees from restaurant industry were employed for this study. The analysis was performed using SPSS and SmartPLS. Correlational analysis was performed which explored the relationship between study variables. A significant positive relationship was found between inclusive leadership, work engagement, positive work reflection and work family positive spillover. Using Process Macro, serial mediation analysis was performed. The results found support for mediatory role of positive work reflection and work engagement independently in relationship between inclusive leadership and work family positive spillover. However, the serial mediation was not achieved indicating that combined effect of work engagement and work reflection did not lead to positive work family spillover. The findings suggest future directions for testing the proposed model using longitudinal analysis to better examine the relationships. Overall, the findings of this study contribute in comprehending the underlying cognitive mechanism which explain the linkage between inclusive leadership and work family positive spillover that has been discounted in prior research.
Keywords: 330; Inclusive leadership; work family positive spillover; work engagement; work reflection; serial mediation; cognitive mechanism; conservation of resource theory